PENGEMBANGAN PRODUK WISATA DENGAN MENGGUNAKAN TEKNIK TOURISM OPPORTUNITY SPECTRUM TERHADAP KEPUTUSAN BERKUNJUNG (Survei Pada Pengunjung Cukang Taneuh/Green Canyon Kabupaten Ciamis) - Trigantiarsyah, Rela; Mulyadi, Hari (Universitas Pendidikan Indonesia, 2012)
Cukang Taneuh located in the village Kertayasa District Cijulang Kudat district is a tourist attraction that environment (ecotourism). Based on data Cukang Taneuh increase the number of tourists during the past four years, but a decline in the percentage of growth in the average number of visits are very significant. 2009 to 2010 the number of percentage increase amounted to only 9.24% of the target achievement of the increase in the number of tourists by 25% in 2010. Not achieving the target of tourist arrivals is presumably due to the lack of development of tourism products so that tourists experience burnout or boredom. One effort to improve and restore the number of tourists is the development of tourism products by using the technique of tourism opportunity spectrum. The purpose of this study was 1) to obtain findings regarding the development of tourism products by using the technique of tourism opportunity spectrum in tourist attractions Cukang Taneuh 2) To obtain findings regarding the decision to visit the tourist attractions Cukang Taneuh 3) To determine the effect of tourism product development by using the technique of tourism opportunity spectrum of the decision to visit the tourist attractions Cukang Taneuh. This research is descriptive and verification, because the method used is explanatory survey method using an ordinal scale. The analysis technique used in this research is the analysis of the path (path analysis), the sampling technique using systematic random sampling method through cross-sectional approach, the samples taken from the overall population of 150 visitors. The study of the hypothesis shows that the development of tourism products by using the technique of tourism opportunity spectrum consisting of accessibility, the characteristics of tourism facilities, social interaction, and the degree of management control has direct and indirect influence on the decision to visit the tourist attractions Cukang Taneuh 93.2% while the remaining 6.8% is influenced by other factors not examined in this study. The dimensions of the development of tourism products by using techniques spectrum of tourism opportunity to get high to low valuation is characteristic of tourism facilities, social interaction, the degree of management control, and accessibility